A BRITE view on the massive O-type supergiant V973 Scorpii: hints towards internal gravity waves or sub-surface convection zones. Issue 1 (19th July 2018) - Ramiaramanantsoa, Tahina; Ratnasingam, Rathish; Shenar, Tomer; Moffat, Anthony F J; Rogers, Tamara M; Popowicz, Adam; Kuschnig, Rainer; Pigulski, Andrzej; Handler, Gerald; Wade, Gregg A; Zwintz, Konstanze; Weiss, Werner W
ABSTRACT: Stochastically triggered photospheric light variations reaching ∼40 mmag peak-to-valley amplitudes have been detected in the O8 Iaf supergiant V973 Scorpii as the outcome of 2 months of high-precision time-resolved photometric observations with the BRIght Target Explorer (BRITE) nanosatellites. The amplitude spectrum of the time series photometry exhibits a pronounced broad bump in the low-frequency regime (≲0.9 d −1 ) where several prominent frequencies are detected. A time–frequency analysis of the observations reveals typical mode lifetimes of the order of 5–10 d. The overall features of the observed brightness amplitude spectrum of V973 Sco match well with those extrapolated from two-dimensional hydrodynamical simulations of convectively driven internal gravity waves randomly excited from deep in the convective cores of massive stars. An alternative or additional possible source of excitation from a sub-surface convection zone needs to be explored in future theoretical investigations.